Perkembangan Material Rotan dan Penggunaan di Dunia Desain Interior - Hartanti, Grace (Bina Nusantara University, 2012)
For most Indonesia people, rattan had long been known, for personal use and trade. It started from raw materials and semi-finished trades, and later it was developed into the finished rattan product trade conducted by the wholesalers in Indonesia. In addition to the processing of rattan in Indonesia, the rattan finished-product trade has also been done widely.The trade agreement that has been made with foreign parties spur the contribution in increasing the state revenue which deserves to be taken into account. In this case, rattan application has grown in the world of Interior Design, for example as furniture and as interior accessories. The use of substitute materials, such as synthetic rattan, is now also widely used to fulfill high demand and product diversity.With the growing numbers of variants of rattan application in interior design field, a research based on qualitative research was applied. Article explores the process of research and rattan is expected to be the mediator in bringing local Indonesian culture to the global world competition. Thus, the state gait could be known more widely, and hopefully could help improving the welfare of Indonesian people into a better place.